3D zero-thickness interface model for fracture of cement-based materials with chemical degradation. (1st March 2022) - Martínez, Ariadna; Liaudat, Joaquín; López, Carlos M.; Carol, Ignacio
Abstract: In the framework of the Finite Element Method, zero-thickness interface elements have been widely used to model fracturing processes in quasi-brittle materials in a broad variety of problems. In particular, interface elements equipped with elastoplastic constitutive laws that account for the softening of the material strength parameters due to the fracturing mechanical work has been proved to accurately reproduce observed fracture propagation behaviour in concrete. Along this line, this paper presents the extension of an existing constitutive law of this kind to include the effect of chemical degradation of the material in the formation of fractures. The law is defined in terms of the normal and shear stresses on the average plane of the crack and the corresponding normal and shear relative displacements. A hyperbolic cracking (plastification) surface in the stress state determines the crack initiation. The softening of the cracking surface is governed by two history variables: an internal variable that accounts for the dissipated fracturing (plastic) work, and an external variable to be provided by a chemical degradation model that accounts for the effect of chemical degradation on the strength parameters. After a detailed discussion of the formulation, the main characteristics of the proposed law are illustrated with a number of academic examples for different combinations of mechanical loading and chemical degradation sequences. The model is finally validated against experimental results from the literature consisting of three-point bending tests performed on mortar samples previously exposed to an aggressive solution for different time periods.